Analisis Pengaruh Service Quality Terhadap Customer Retention - Jana, Reva Rian, Dr. Anton Agus Setyawan, SE.,MSi (2016)
The purpose of this study was to analyze service quality like "tangibles, reliability, ressponsiveness, assurance, empathy" and food quality to customer retention in KFC Solo Square. The design of this study is survey and a confirmatory study. The population in this study are all consumers KFC Solo Square. The research sample of 100 respondents. The sampling method used non probability sampling with purposive sampling approach that the sampling design in which elements in the population do not have opportunities to be selected into the sample are known. Methods of data analysis used in this study is multiple linear regression analysis, t-test, F-test and coefficient of determination. The results showed that service quality has positive effect on customer retention. The higher service quality offered KFC Solo Square increasing effect customer retention. This means that with increased service quality such as cleanliness and neatness of the employees, the products are standardized and reliable, served quickly and precisely to order, able to evoke consumer confidence in purchasing products and result in increased customer retention. Food quality positive effect on customer retention. That is, the higher the quality of food served increasing higher customer retention. This means that the food was more delicious menu, pay attention to nutrition food offered, more fresh food provided, creating the smell of food that is able to arouse consumer tastes, then the presentation of the food is made more attractive.